1992
DOI: 10.1002/1097-0142(19921101)70:9<2263::aid-cncr2820700909>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Do the tumor cells of hepatocellular carcinomas dislodge into the portal venous stream during hepatic resection?

Abstract: Background. The current study was undertaken to investigate whether or not tumor cells are dislodged into the portal venous stream during hepatic resection for hepatocellular carcinomas. Methods. A catheter was placed using echo guidance into the portal branch through the mesenteric vein in 31 patients. Cytologic examinations were done on multiple blood samples at various operative stages. Results. Tumor cells were recovered in 7 of 31 patients in whom the tumor sizes were more than 5 cm and portal invasions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 12 publications
0
76
0
1
Order By: Relevance
“…Indeed, dissemination of cancer cells from primary HCC into the portal vein during surgical resection has been observed. 20 Nevertheless, disseminated cells do not always survive in the circulation and form metastatic sites, although anchorage-independent growth and rapid growth of cancer cells after surgical resection may be important factors for early [21][22][23][24][25][26] such as tumor volume, histopathologic dedifferentiation, microscopic invasiveness, high cellular proliferation, and p53 mutation. A high serum concentration of ␣-fetoprotein, which reflects tumor volume, was reported to be a predictor of early disease recurrence, and a previous report showed that p53 mutation was associated with the progression of HCC as a late event in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dissemination of cancer cells from primary HCC into the portal vein during surgical resection has been observed. 20 Nevertheless, disseminated cells do not always survive in the circulation and form metastatic sites, although anchorage-independent growth and rapid growth of cancer cells after surgical resection may be important factors for early [21][22][23][24][25][26] such as tumor volume, histopathologic dedifferentiation, microscopic invasiveness, high cellular proliferation, and p53 mutation. A high serum concentration of ␣-fetoprotein, which reflects tumor volume, was reported to be a predictor of early disease recurrence, and a previous report showed that p53 mutation was associated with the progression of HCC as a late event in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…were as follows: 72.9% and 83.3% at 1 year; 58.3% and 83.3% liver. [7][8][9] However, recurrence is not rare even in cases with at 2 years, respectively (P õ .05) (Fig. 5).…”
Section: Methodsmentioning
confidence: 99%
“…28,29 IM is thought to develop through tumor cell dissemination through the portal vein. 30 Previous studies using the mouse IM model indicate activation of RhoA 21 and AKT, 31 and overexpression of cortactin 32 Reduced TGFBR2 expression correlated with portal vain invasion in HCC cases, and poorly differentiated HCC cells showed lower TGFBR2 expression compared with well-differentiated cells. This suggests that HCC cells, with reduced TGFBR2 expression, seem to be more invasive and may promote IM.…”
Section: Tgfbr2 Expression In Hccsmentioning
confidence: 99%